Fusion Food Book Development Based Contextual Learning: How are the Feasibility of Experts and Student Responses? - Pangesthi, Lucia Tri; Miranti, Mauren Gita; Handajani, Sri; Nur Aini, Annisa (Universitas Pendidikan Ganesha, 2024)
Some teachers are still lacking in developing teaching materials and only use them from articles and recipe books, so they do not contain clear and appropriate learning strategies according to the material in culinary learning. This has an impact on low student learning outcomes. This study aims to develop and analyze the feasibility of textbooks from the results of expert assessments, which state that the textbooks are valid, practical, and effective for use in the learning process. This type of research is research and development, consisting of 10 stages. The validity of the textbooks was determined by 6 media experts and 6 material experts from academia and industry. Validity was analyzed using the content validity index (CVI) and inter-rater reliability (IRR) using the Cohen Kappa agreement coefficient (K). The research sample used to see the effectiveness of the textbooks was 102 students of the Culinary Arts Department. The study results showed that, first, the validity and reliability of the developed teaching materials were categorized as very valid. Second, the practicality of the developed teaching materials was categorized as practical. Third, the effectiveness of the developed teaching materials was categorized as effective. Based on the study results, the teaching materials developed have good quality and meet the standards of teaching material eligibility to improve students' understanding of the concept of fusion food. The implications of research on developing Fusion Food Book based on contextual learning have significant potential to improve the learning process.